Enantioselective synthesis of chiral 3-alkyl-3-nitro-4-chromanones via chiral thiourea-catalysed intramolecular Michael-type cyclization. Issue 34 (13th August 2021) - Chen, Huiqing; Tang, Jie; Liu, Ting; Yu, Li-Fang; Xing, Dong; Yang, Fan
Abstract : The enantioselective synthesis of chiral 3-alkyl-3-nitro-4-chromanones is realized via a chiral thiourea-catalysed intramolecular Michael-type cyclization reaction. Abstract : Herein we report an enantioselective method for the rapid construction of chiral 3-nitro-4-chromanones via a chiral thiourea-catalyzed intramolecular Michael-type cyclization reaction. With this method, a series of 3, 3-disubstituted-3-nitro-4-chromanones bearing contiguous C2/C3 stereocenters were obtained with high diastereoselectivities and good to excellent enantioselectivities. In vitro biological evaluations indicated that the chiral amide derivative of the product showed more potent antitumor activities than both the racemic and the corresponding enantiomers, showcasing the high influence of enantioselective methodology development toward medicinal studies.